Effects of Emtricitabine/Tenofovir on Bone Mineral Density in HIV-Negative Persons in a Randomized, Double-Blind, Placebo-Controlled Trial - Kathleen Mulligan (2018)
© 2015 The Author 2015. Background. Daily preexposure prophylaxis (PrEP) with oral emtricitabine and tenofovir disoproxil fumarate (FTC/TDF) decreases the risk of human immunodeficiency virus (HIV) acquisition. Initiation of TDF decreases bone mineral density (BMD) in HIV-infected people. We report the effect of FTC/TDF on BMD in HIV-seronegative men who have sex with men and in transgender women. Methods. Dual-energy X-ray absorptiometry was performed at baseline and 24-week intervals in a substudy of iPrEx, a randomized, double-blind, placebo-controlled trial of FTC/TDF PrEP. Plasma and intracellular tenofovir concentrations were measured in participants randomized to FTC/TDF. Results. In 498 participants (247 FTC/TDF, 251 placebo), BMD in those randomized to FTC/TDF decreased modestly but statistically significantly by 24 weeks in the spine (net difference, -0.91% [95% confidence interval CI, -1.44% to -.38%]; P =. 001) and hip (-0.61% [95% CI, -.96% to -.27%] , P =. 001). Changes within each subsequent 24-week interval were not statistically significant. Changes in BMD by week 24 correlated inversely with intracellular tenofovir diphosphate (TFV-DP), which was detected in 53% of those randomized to FTC/TDF. Net BMD loss by week 24 in participants with TFV-DP levels indicative of consistent dosing averaged -1.42% ± 29% and -0.85% ± 19% in the spine and hip, respectively (P < . 001 vs placebo). Spine BMD tended to rebound following discontinuation of FTC/TDF. There were no differences in fractures (P =. 62) or incidence of low BMD. Conclusions. In HIV-uninfected persons, FTC/TDF PrEP was associated with small but statistically significant decreases in BMD by week 24 that inversely correlated with TFV-DP, with more stable BMD thereafter.